2009
DOI: 10.1177/0886260509336963
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Behaviors and Reasons for Help Seeking Reported by a Representative Sample of Women Victims of Intimate Partner Violence in New Zealand

Abstract: Efforts to understand and support the process of help seeking by victims of intimate partner violence are of considerable urgency if we are to design systems and responses that are capable of actively and appropriately meeting the needs of victims. Using data from the New Zealand Violence Against Women Study, which drew from a representative general population sample of women aged 18 to 64 years, the authors report on the help-seeking behaviors of the women who had ever in their lifetime experienced physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
249
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(291 citation statements)
references
References 24 publications
27
249
2
4
Order By: Relevance
“…Considerably more victims report telling informal sources of support about their experiences. The same pattern has been reported among both men and women in international research (Ullman, 2007;Postmus et al, 2009;Ansara and Hindin, 2010;Fanslow and Robinson, 2010;McCart et al, 2010). In accordance with this a need to talk to professionals about their victimization was expressed by some of the men in study IV, some also said that the support they received from family and friends was enough.…”
Section: The Risk Of Medicalizationsupporting
confidence: 63%
See 2 more Smart Citations
“…Considerably more victims report telling informal sources of support about their experiences. The same pattern has been reported among both men and women in international research (Ullman, 2007;Postmus et al, 2009;Ansara and Hindin, 2010;Fanslow and Robinson, 2010;McCart et al, 2010). In accordance with this a need to talk to professionals about their victimization was expressed by some of the men in study IV, some also said that the support they received from family and friends was enough.…”
Section: The Risk Of Medicalizationsupporting
confidence: 63%
“…In line with this, several of the men in study IV reported that they had been reluctant to seek help and that it had been difficult to disclose their victimization but when they did, it was a relief. Another similarity with previous studies involving female victims of intimate partner violence was that shame and fear of negative consequences were often reported as strong factors tipping the balance towards not disclosing (Hathaway et al, 2002;Liang et al, 2005;Schreiber et al, 2009;Fanslow and Robinson, 2010).…”
Section: Health Care System's Response To Victims Of Interpersonal VImentioning
confidence: 65%
See 1 more Smart Citation
“…Proposals include greater linkage of victims to resources and increased feelings of safety among victims by enhancing coordinated community responses (Boal & Mankowski, 2014;Klevens, Baker, Shelley, & Ingram, 2008). Such resources may be needed, as a national study found that onethird of women who reported IPV to officials received no formal services or assistance (Fanslow & Robinson, 2010). Recent debates have also appeared in professional journals about whether or not it is appropriate to involve victims in aspects of treatment.…”
Section: Victim Contactmentioning
confidence: 99%
“…Victims of PA often experience tremendous declines in physical and psychological health following repeated acts of aggression (Lawrence et al, 2012). Additional concerns for BIP organizers are victim characteristics that may prevent reporting as well as fears and past negative experiences with police responders, minimization of the severity of violence, the perceived requirement to end the relationship, and fears of repercussions from the perpetrator (Fanslow & Robinson, 2010;Fugate, Landis, Riordan, Naureckas, & Engel, 2005). Consequently, victim populations require unique consideration when devising plans for assessment and intervention in the legal as well as therapeutic domains.…”
Section: Victim Contactmentioning
confidence: 99%